CHARACTERIZATION OF BIOBRICKETS FROM COCONUT SHELL AND WOOD SAWDUST - Siti Fatimah (Universitas Lampung Jl. Prof. Dr. Sumatri Brojonegoro No.1 Bandar Lampung, 2023)
Inhabitant increase quickly causes so much request for energy though petroleum is more less because of humans exploration. Biobriquette can be considered as the best option for alternative renewable energy produced from organic materials or biomass that is underutilized. Biomass wastes that can be used as materials for making biobriquettes include coconut shells, wood sawdust, oil palm shells, rice husks and other organic materials. This study aims to assess the quality briquettes of coconut shell and pollen teak with adhesive of sticky tapioca flour The experimental design is the mass variation of wood sawdust (10%, 20%, 30%, 40%, 50%), and coconut shell (50%, 40%, 30%, 20%, 10%). The parameters used are fixed carbon, volatile matter and calorific value that measured by Oxygen Bomb Calorimeter. The results showed that the highesr fixed carbon was 33,793% with the composition of coconut shell : wood sawdust (10% : 50%), the lowest volatile matter was 49,896% with the composition of coconut shell : wood sawdust (10%:50%) and the highest calorific value of 6392 cal/g with coconut shell composition: wood sawdust (10%: 50%). Thus the coconut shell and sawdust can be used as alternative raw materials in making biobriquettes. From these results, this biobriquet meets the Indonesian National Standard (SNI) 01-6235-2000.Keywords: Briquette, calorific value, fixed carbon, volatile matter.